Hume’s Law, Moore’s Open Question and Aquinas’ Human Intellect - Trujillo Werner, Augusto (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
This article is about Aquinas’ practical doctrine on two great current philosophical difficulties that lie at the basis of contemporary ethical debate. Such as Hume’s Is-ought thesis and Moore’s radical synthesis, the Open question. The thomistic possible solution can be found in the triple function of the human intellect, theoretical and practical at the same time: a) To apprehend the ontological or intellectual notions ens, verum and bonum; b) To formulate the first theoretical and practical principles; c) And to rule that the ontological and intellectum good be done and the opposite avoided.
Keywords: Hume; Moore; Aquinas; Ontology; Ethics; Apprehension; Ens; Verum; Bonum